Quantitative and Continuous Analysis of ATP Release from Blood Platelets with Firefly Luciferase Luminescence - Higashi, Terumasa; Isomoto, Akio; Tyuma, Itiro; Kakishita, Eizo; Uomoto, Michiko; Nagai, Kiyoyasu (Thrombosis and Haemostasis, 1985)
An analytical method was devised to determine the entire course of the adenosine-triphosphate (ATP) release from blood platelets based on a continuous measurement of firefly luciferase luminescence. The equation of the release reaction was derived after due consideration of substrate (ATP) consumption and product (oxyluciferin) inhibition on the luciferase reaction as follows: C, = vt × (Km/Vmax) × (I + It/Ki) + It where Ct is the total concentration of the released ATP at time t, vt is the velocity of the luciferase reaction at time t and is directly measured, It is the concentration of oxyluciferin at time t, and Vmax, Km and Ki are constants. C, of the gel-filtered platelet suspension (GFP) could be determined by substituting vt and It as functions of t. The effects of albumin and temperature on the reaction were also studied.
Keywords: ATP release from blood platelets; Firefly luciferase luminescence; Time-course kinetics; Product inhibition